Міжкультурна взаємодія в контенті медіа багатонаціонального регіону - Орлов, Андрій Володимирович; Орлов, Андрей Владимирович; Orlov, Andrii V. (Східноєвропейський національний університет імені Лесі Українки, 2013)
Вивчення ролі місцевих медіа в процесі підтримки міжетнічної злагоди й толерантності в місті Мелітополі як еталонному полікультурному середовищі спричинене актуальністю всебічного дослідження феномену комунікації в контексті соціокультурної реальності нашого часу та полілогу культур. За результатами контент- аналізу повідомлень місцевих ЗМІ (газета «Мелітопольські відомості» й Телерадіокомпанія «МТВ-плюс») зроблено висновки про те, що суспільний розвиток регіону значною мірою визначається рівнем розвитку міжетнічного спілкування та, отже, залежить від соціально-правової складової частини функціонування засобів масової інформації. Місцеві ЗМІ, зазвичай, подають лише позитивну інформація щодо етнічних питань; вона має низький рівень, та все ж сприяє підтримці міжнаціональних стосунків. The necessity of comprehensive study of the phenomenon of communication in the context of socio-cultural reality of our time and polylogue cultures becomes important in light of peculiarities of the development of communication processes under the condition of the formation of new civilizational relations. The intercultural communication is of special importance in multinational regions, one of which is Zaporizhia Priazovye. This study is aimed to explore the role of local media in the process of maintaining ethnic harmony and tolerance in Melitopol as a reference multicultural environment. Conclusion is made on the basis of content analysis of local media reports (newspaper «Melitopol’s’ki vedomosti» and TV channel «MTV-plus»). It shows that the social development of the region is largely determined by the development level of inter-group and inter-ethnic communication and, therefore, it depends on the socio-legal functioning component of the media. Local media, realizing the specific area of their distribution, does not release information that could aggravate inter-ethnic relations. Moreover, information about ethnic subjects is usually given only in a positive manner. It is low-leveled but still promotes to regulate international relations.
The Intercultural Interaction Content of Media in Multi-Ethnic Region
Keywords: етнічність; міжкультурна взаємодія; толерантність; медіа (ЗМІ); повідомлення; еthnicity; intercultural co-operation; tolerance; mass-media; report